P230 Facilitating End-Of-Life Discussions in Users of Home Mechanical Ventilation That Have a Life-Limiting Neuromuscular Disease. (19th November 2012) - Palmer, J; Stephen, N; Endacott, R
Abstract : Introduction and Objectives: There are many individuals living in the United Kingdom with a neuromuscular disease which will cause their death. Many use home mechanical ventilation (HMV). Discussing end-of-life care with patients with life-limiting disease is currently high on the health agenda. Whilst the published guidance does not provide evidence that patients wish to be involved in these discussions, the knowledge base tends to support it. There are few studies which specifically investigate whether those with progressive neuromuscular disease want to be involved or what facilitates such conversations. We examined the experience of HMV patients with neuromuscular disease with regards end of life discussions. Methods: A generic qualitative research approach was employed. Purposive sampling was utilised. Individuals, volunteered to participate in a face-to-face interview. The interview transcripts were analysed using a thematic content approach to identify common themes. Results: Interviews were conducted with 9 individuals; 5 male, 4 female with a mean age of 58 years (range 31–74). Five participants had Motor Neuron Disease (MND). Four had less progressive disease. Two participants used continuous tracheostomy ventilation; the others used HMV predominantly at night. Five denied that they had taken part in a professional led end-of-life conversation. Four participants have since died. The key findings indicate that for constructive dialogue to take place most individuals required a prompt or cue from a care professional. Not all had one. Once received most patients would engage in conversations as long as the timing, conditions and professional were appropriate. The need to remain positive and to receive adequate information were strong themes throughout the interviews. The presence of relatives or significant others was a barrier to productive conversations in those with more stable disease but a facilitator to those with MND. Conclusion: Despite the need for individuals to remain positive, useful discussions can take place if patients are approached to do so by a knowledgeable professional with the correct skills at an appropriate place in the disease trajectory. If such discussions do take place then patients can find these rewarding and they can have a positive effect on their lives.